STRUCTURAL AND FUNCTIONAL ADVANCES IN SURGICAL SUTURE MATERIALS - Mardonov Jamshid Normurotovich; Mahmudov Kodirjon Oltinboevich; Khujamberdiev Abdusalom Ubaydullaevich; Abdullaeva Mokhima Abdullaevna; Nabijonov Bakhodirbek Sodikjon ugli (Western European Studies, 2025)
Recent advances in surgical practice have been closely associated with the development of innovative suture materials exhibiting improved mechanical, biological, and functional properties. Beyond their primary role in tissue approximation, surgical sutures actively interact with the wound microenvironment, influencing inflammatory responses, microbial adhesion, and regenerative processes. This review focuses on the structural and functional evolution of surgical suture materials, with particular emphasis on filament architecture, degradation mechanisms of absorbable polymers, surface modifications, and emerging smart technologies. Based on current experimental and clinical literature, the properties and performance of monofilament and multifilament sutures, absorbable and non-absorbable materials, as well as antibacterial, drug-eluting, and nanostructured coatings are critically analyzed. In addition, novel concepts such as stem cell-loaded sutures, electronic and sensor-integrated sutures, and photobiomodulation-assisted modulation of suture–tissue interactions are discussed as promising future directions in surgical biomaterials research. The integration of advanced materials science and biomedical engineering approaches into suture design is expected to enhance wound healing, reduce postoperative complications, and contribute to the development of next-generation multifunctional surgical sutures.
Keywords: surgical suture materials; filament structure; antibacterial coatings